From Inception to Realization: NIST's Post-Quantum Cryptography Standardization - Renita J; Edna Elizabeth N; Suganya Annadurai, (Indian Journal of Cryptography and Network Security (IJCNS), 2025)
Cryptography is a term that safeguards the security of electronic banking transactions, and emails, and most importantly our country relies on cryptography for national security purposes. Post Quantum Cryptography (PQC) has a major aim of developing newer cryptographic schemes that make the cryptosystem secure against quantum computers. This is a state-of-the-art research topic, and it is encouraged by some security agencies like the National Security Agency (NSA). This paper presents a concise and up-to-date review of post-quantum cryptographic (PQC) algorithms submitted to the National Institute of Standards and Technology (NIST) for standardization. Highlighting the need for cryptographic resilience in the era of quantum computing, the study focuses on the technical evaluation of candidate algorithms, including their performance in terms of time and space efficiency. It also examines the progression of these algorithms through NIST’s multi-round selection process, highlighting key developments and implementation challenges. The paper aims to provide researchers with a clear overview of the current state of PQC standardization and the practical considerations involved in deploying secure, quantum-resistant cryptographic solutions.